Molecular Detection of Helicobacter Pylori in Sheep at ALMuthana Province of Iraq - Ftima Atiya Kareem; Nabeel M.H. Al- Maaly (Indian Journal of Forensic Medicine & Toxicology, 2021)
Helicobacter pylori (H. Pylori) was discovered in 1982. Over 50% of the world population is infected bythis bacterium. H. Pylori is the main cause of gastritis, peptic ulcers, and gastric cancer in human. Foodswith animal origins play a substantial role in the transmission of H. Pylori. The present investigation wascarried out to study the molecular detection of H.pylori in stomach gastric tissue of the sheep.Collectingof the samples occur randomly from various area of Al-Muthana province slaughter house(AL-Muthana,AL-Khudur, AL-Rumethah)from October 2019 to February 2020 . One hundred and fifty (n 75 male, n 75female) abomasums samples were collected and dissection in aseptic manner then stored in deep freeze(Liquid nitrogen -196) until processing and analyzed for the presence of 16s RNA and VACA genotypes.This study showed that the Prevalence of H. Pylori in the gastric samples of sheep at slaughterhouses(Al-Muthana, Al-Khdur, Al-Rumethah) were (9 positives) 18 % and (7) 14%, (15) 30% respectively. Themost commonly detected genotypes in the gastric samples of slaughterhouses were 16s RNA (20.67%)in ewes(25.33%) . AL-Rumetha was the most commonly detected H. Pylori (30%). Results showed thatgastric tissue of sheep can act as a reservoir to H. Pylori and disseminate the pathogen in feces and milk thentransmitted to human during uses of unpasteurized milk ,or meat .samples could be the potential sources ofvirulent strains of H. Pylori. Application of sanitary measures in the storage, transportation and sale of meatis essential for reducing the levels of H. Pylori cross contamination.